Studying late medieval history - Wood, Cindy., author.
1 online resource (xii, 229 pages)
Keywords: "Studying Late Medieval History is an introduction for undergraduate history students wishing to understand the major topics in late medieval history. Examining the period from 1300-1550, this introductory guide offers an overview of 250 years of transformation, which saw technology, borders and ruling dynasties across the continent change"--Provided by publisher.